KAJIAN EFISIENSI AGRONOMIS PADI (Oryza sativa L.) VARIETAS INPARI GEMAH PADA TANAH SAWAH BERSTATUS P DAN K TINGGI MELALUI APLIKASI ORGANOMINERAL FLY ASH DENGAN PEMUPUKAN NPK - Eriani Septi Dwika Putri; Ir. Friza Elinda; Dewi Jayagma Ilham; Ir. Ismon L (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the efficiency level of applying organomineral fly ash combined with NPK fertilizer in improving rice yield on paddy soils with high phosphorus (P) and potassium (K) status. The research was conducted at Green Hill Arya Housing Complex, Tanjung Harapan District, Solok City, from November 2025 to March 2026. A Randomized Complete Block Design (RCBD) with five replications was used. The treatments consisted of five levels of NPK fertilizer application (0, 100, 200, 300, and 400 kg NPK ha⁻¹) combined with 5 tons ha⁻¹ of organomineral fly ash. The observed parameters included plant height, number of tillers, number of panicles, panicle length, number of grains per panicle, weight of filled grains, weight of empty grains, grain weight percentage, 1,000-grain weight, fresh straw weight, dry straw weight, pot yield, and agronomic efficiency. The results showed that the application of organomineral fly ash combined with 3.3 g NPK (A4) was the most efficient application rate for the Inpari Gemah rice variety grown on Solok paddy soils. The application of organomineral fly ash combined with 4.4 g NPK (A5) had a highly significant effect on 1,000-grain weight, while the application of organomineral fly ash combined with 3.3 g NPK (A4) had a highly significant effect on filled grain weight and production yield. Furthermore, the application of organomineral fly ash combined with 4.4 g NPK (A5) significantly affected the number of panicles and fresh straw weight, while the application of organomineral fly ash combined with 2.2 g NPK (A3) significantly affected the number of grains per panicle, and the application of organomineral fly ash combined with 3.3 g NPK (A4) significantly affected dry straw weight. In contrast, the treatments had no significant effect on plant height, number of tillers, panicle length, empty grain weight, and grain weight percentage.